Bilateral caudal zona incerta nucleus stimulation for essential tremor: outcome and quality of life. Issue 8 (1st February 2011) - Plaha, Puneet; Javed, Shazia; Agombar, David; O' Farrell, Genevive; Khan, Sadaquate; Whone, Alan; Gill, Steven
Abstract : Background: Over the past few years, bilateral stimulation of the caudal or motor part of the zona incerta nucleus (cZI) has been performed by the authors in patients with essential tremor (ET). Outcomes including quality of life data in 15 patients with a follow-up period of up to 84 months (mean 31.7±28.6 months) are presented. Methods: 15 consecutive ET patients underwent MRI guided bilateral cZI deep brain stimulation implantation. Patients were assessed by applying the Fahn–Tolosa–Marin Tremor Rating Scale and the Short Form Health Survey-36 (SF-36) to assess quality of life. Results: The total tremor score improved by 73.8% (p<0.0001). The part A score (items 1–9) improved by 86.6% (p<0.0001). Postural tremor improved by 88.2% (p<0.0001) and action tremor by 82.2% (p<0.0001). The part B score, which evaluates the functional activities of the upper limbs, improved by 60.1% (p<0.0001). Part C score, which evaluates the activities of daily living, improved by 80.0% (p<0.0001). The SF-36 physical component score improved by 23.7% (p<0.0001) and the mental component score by 22.4% (p<0.0001). There was one wound infection and three patients developed stimulation related transient dysarthria. None developed any disequilibrium or tolerance to stimulation. Conclusion: Bilateral cZI stimulation is safe and effective in suppressing the postural and action component of ET. It is associated with a low incidence of stimulation related complications and patients do not develop tolerance to stimulation with maintained clinical benefit over a follow-up period of up to 7 years.